An expert screen design and evaluation assistant that uses knowledge-based backtracking - Ngo,, DCL; Law,, BL (2003)
Current user interface builders provide only low-level assistance, because they have knowledge of neither the application, nor the principles by which interface elements are combined effectively. We describe a design tool that unites the knowledge components essential for effective dialog box layout. The knowledge base model consists of (1) style knowledge, which provides design-time constraints on interface specifications; (2) style application system, which handles the actual layout of dialog boxes based on the style knowledge base; (3) design knowledge, which provides quantitative metrics to analyse the spatial properties of the dialog box layout; and (4) design evaluation system, which uses evaluation metrics to compare and evaluate alternative designs. As our empirical study shows, the redesigns using the design tool had significant effect on the preference data. (C) 2002 Elsevier Science B.V. All rights reserved.